(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Teaching English to young learners is a crucial step in their cognitive and linguistic development. This article elaborates on effective teaching methods, including play-based learning, TPR, technology integration, and parental involvement. Each method is discussed in detail, offering practical insights and highlighting its significance. The benefits of teaching English at an early age, particularly in the context of Uzbekistan, are explored. The article concludes with a focus on the role of these methods in creating a solid foundation for global communication skills.